Blood Level of Glial Fibrillary Acidic Protein (GFAP) Does not Correlate With Disease Progression in a Rat Model of Familial ALS (SOD1G93A Transgenic) - Jeffrey, Jeremy; D'Cunha, Hannah; Suzuki, Masatoshi (Frontiers in Neurology, 2018)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by specific loss of motor neurons in the spinal cord and brain stem. Currently, there are limited options for treating ALS and further investigation of the disease etiology and ALS disease progression need to be completed. There is an urgent need to identify biomarkers to detect and study disease progression in ALS. Glial fibrillary acidic protein (GFAP) is an intermediate filament protein that is expressed by a number of cells related to the central nervous system including glial cells and ependymal cells. Recent studies indicated that significant levels of GFAP protein were detected in peripheral tissues such as skeletal muscle. In this study, we hypothesized that levels of GFAP in blood represent a biomarker of disease progression in ALS. To test this specific hypothesis, we used a rat model of familial ALS (SOD1G93A transgenic), which has been extensively used to understand the complexity of this devastating disease. Disease progression in a cohort of male and female SOD1G93A transgenic rats was monitored by motor function, and blood samples were collected when these animals reached disease end-stage. We measured GFAP protein levels by ELISA and found no correlation between GFAP concentration and disease progression in either serum and plasma samples of SOD1G93A transgenic. Further investigation would be required in order to implicate blood GFAP as a potential biomarker for ALS.